Keabsahan Penuntutan Bebas Dalam Kasus Valencya - Lusia Sulastri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
Dropping charges is a new landmark for Indonesian law. This practice indeed has not been regulated in the Criminal Procedure Code, since it is the court’s role to decide whether someone is guilty or not guilty, moreover the Prosecutor's Office is the one initially pursuing charges for Valencya with Article 45 verse (1) in conjunction with Article 5 letter B of Law No. 23 of 2004 on The Elimination of Domestic Violence, but then decided to do the opposite. Therefore, this practice is an interesting to study. This study indicates that the existence of an acquittal had shown that the prosecutor's dominus litis in carrying out prosecution. The attorney general has a valid legal basis, namely Article 35 letter c of Law Number 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia through the implementation of th principle of opportunity to a case. Thus, the acquittal of Valencya is valid despite it being unusual. The acquittal of Valencya rises a discovery and legal reform, to prosecutor's dominus litis in carrying out prosecutions not only to delegate criminal cases to the District Court in terms of and according to the method regulated by law, but also prosecuting for acquittal, meaning that the Public Prosecutor is given the right to use a sense of crisis in determining a criminal case and the Public Prosecutor may demand the release of a defendant for justice based on progressive law.